2022
DOI: 10.1039/d2se00997h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical ammonia synthesisvianitrate reduction on perovskite LaxFeO3−δwith enhanced efficiency by oxygen vacancy engineering

Abstract: It is a novel and challenging project to seek an effective electrocatalyst to synthesize the valuable ammonia from the harmful nitrate in the wastewater. This work innovatively applied the perovskite...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…42 Recently, some studies have shown that the introduction of oxygen vacancies in an electrocatalyst can signicantly boost its NO 3 ER activity. 25,[43][44][45][46] The main mechanism has been well recognized to be that the oxygen atoms in nitrate tend to ll the oxygen vacancies in the catalyst, which can effectively capture nitrate and promote the adsorption and reduction of nitrate, weaken the N-O bond and restrict the formation of by-products, thus improving the selectivity and efficiency of ammonia synthesis by NO 3 ER. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Recently, some studies have shown that the introduction of oxygen vacancies in an electrocatalyst can signicantly boost its NO 3 ER activity. 25,[43][44][45][46] The main mechanism has been well recognized to be that the oxygen atoms in nitrate tend to ll the oxygen vacancies in the catalyst, which can effectively capture nitrate and promote the adsorption and reduction of nitrate, weaken the N-O bond and restrict the formation of by-products, thus improving the selectivity and efficiency of ammonia synthesis by NO 3 ER. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22] A few perovskite oxides have been applied in NO 3 ER, such as La 2 CuO 4 , BiFeO 3 , and La x FeO 3−d . [23][24][25] Despite some progress having been made, the NO 3 ER performance is still unsatisfactory and needs further improvement. Generally, in the category of perovskite oxides, beneting from their extremely abundant crystal structures and electronic features (e.g., coordination, spin state, valence state), cobalt-based perovskite oxides exhibit the most varied physicochemical properties, occupying a very important position in electrocatalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2d) can be deconvoluted into three peaks at 529.32 eV (O1, lattice oxygen), 531.17 eV (O2, defective oxygen), and 532.36 eV (O3, hydroxyl oxygen), which correspond with the O species in Cu-O and Co-O, the vacant O species caused by the detachment of some oxygen atoms, and the oxygen species from chemisorbed and physiosorbed water on or within the surface, respectively. 38,39 Compared to CoO/CF and CuO x /CF (Fig. S2 †), the CoO-CuO x /CF heterostructure has the highest ratio of vacant oxygen species, while the percentage of lattice oxygen and hydroxyl oxygen is lower.…”
Section: Resultsmentioning
confidence: 99%
“…Yin and co‐workers prepared LaFeO 3 with different contents of oxygen vacancies via engineering the La‐deficiency. [ 192 ] High La deficiency (10%) resulted in a high content of oxygen vacancies, which promoted e‐NO 3 RR, suppressed competing HER, and improved the ammonia yield. Similar results were found in other perovskite oxides for e‐NO 3 RR.…”
Section: Catalysts For E‐no3rrmentioning
confidence: 99%